Enhanced photocatalytic activity of graphene oxide decorated on TiO 2 films under UV and visible irradiation - Yoo, Dae-Hwang; Cuong, Tran Viet; Pham, Viet Hung; Chung, Jin Suk; Khoa, Nguyen Tri; Kim, Eui Jung; Hahn, Sung Hong (Current applied physics, 2011)
Photocatalytic TiO 2 films were prepared using RF magnetron sputtering and three kinds of graphene oxide (GO) solutions with different concentration of 0.05 mg GO, 0.03 mg GO, and 0.01 mg GO in 10 ml ethanol were coated on TiO 2 films, respectively. Structures and morphologies of the samples were examined by AFM, SEM, and Raman and photocatalytic properties under UV and visible irradiation were examined respectively. The efficiency of the photodegradation is enhanced when TiO 2 thin film was coated with GO, it is related to its giant π-conjugation system and two-dimensional planar structure and efficient charge separation by coating GO. The maximum photodegradation rate was observed for TiO 2 thin film coated with 0.03 mg GO. It is attributed to the increase of absorbance and scattering of photons through excess carbon in the photosystem. ► Enhancement of photocatalytic activity π-conjugation and two-dimensional structure. ► Enhancement of photocatalytic activity by charge separation and transportation. ► Decreased activity at high GO by increase of absorbance/scattering of photons.